2016
DOI: 10.3390/rel7020016
|View full text |Cite
|
Sign up to set email alerts
|

Religious Groups as Interest Groups: The United States Catholic Bishops in the Welfare Reform Debate of 1995–1996 and the Health Care Reform Debate of 2009–20101

Abstract: Abstract:The United States has a long history of religious influence on public policy: the anti-slavery movement, progressivism, prohibition, civil rights, abortion, school vouchers, school prayer and nuclear disarmament are all issues that have involved religion and religious groups in policymaking. In recent decades, the number of religious interest groups (as well as interest groups in general) has greatly expanded, but the role that the religious organizations play as interest groups in the policy arena ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…30 These groups did not see themselves as traditional interest groups since they organized to promote moral positions rather than derive material benefits. 31 Subsequently, religious interest groups have less trouble with "free-rider" issues than other groups.…”
Section: Theoretical Overviewmentioning
confidence: 99%
“…30 These groups did not see themselves as traditional interest groups since they organized to promote moral positions rather than derive material benefits. 31 Subsequently, religious interest groups have less trouble with "free-rider" issues than other groups.…”
Section: Theoretical Overviewmentioning
confidence: 99%
“…When it acts in the guise of a membership interest group, as well, the Catholic Church displays distinctive features, as it can rely upon two kinds of membership: a narrower one, depending on the institutional organization made up by Bishops, and a wider one, made up by the faithful (Cammisa & Manuel, 2016). As regards the latter, two aspects are worth highlighting: one concerning the ways membership is recruited, another concerning the membership's size.…”
Section: Classification Membership Representationmentioning
confidence: 99%
“…Finally, the Catholic Church has specific features also when it acts as a public interest group, since, unlike the conventional ones, usually focusing on just one cause (e.g., pacifists, environmentalists, those protecting human rights), it is engaged with several causes at the same time. This, as well, stems from the Church's definition of "public good," rooted in its spiritual vision of the world and translated into such ecumenical objectives as peace, human rights, free immigration, disarmament, universal welfare, and abolition of death penalty (Cammisa & Manuel, 2016). The strong moral beliefs on problems perceived as public and the presence of solutions being in line with the Evangelic proposed by the Catholic Church may also lead to clashes with decision-makers (Himes, 2006).…”
Section: Classification Membership Representationmentioning
confidence: 99%
“…One survey found that 75% of faith-based organizations served welfare recipients, with services ranging from food assistance to treatment for mental health and substance abuse (Allard 2007, 317). Catholic groups in particular have been vocal in their opposition to some tenets of welfare reform (Cammissa and Manuel 2016, 14). I anticipate that service-based organizations will be in favor of welfare rules that make accommodations for recipients who have experienced domestic violence.…”
Section: Datamentioning
confidence: 99%